Pelatihan Digitalisasi Dan Branding Umkm Di Dusun Jayan Imogiri Yogyakarta - Zenobia, Zhillan Fadhillah; Gunawan, Taufik; Susanti, Putri Selvia Ghita; Qoyyimah, Isfalana Firli Nur; Maharani, Intan; Micola, Imanda Julian; Aditya, Kastka; Agustin, Sinta Dwi Febri; Wati, Adinda Ranicha; Triadiyansyah, Arif; Suryani, Lilis (Universitas Muhammadiyah Yogyakarta, 2025)
In the midst of increasingly fierce business competition, the use of digital platforms is a tool that we must make the most of. Digitalization has become a fundamental factor in the development of Micro, Small and Medium Enterprises (MSMEs) in the modern era. The main problem of MSMEs in Jayan Hamlet is the lack of understanding of the utilization of digital platforms such as social media and e-commerce that allow MSMEs to reach a wider range of customers without geographical boundaries. The purpose of this activity is to increase the capacity and skills of MSME players through training and mentoring, in order to compete in local and regional markets. In addition, digitalization helps MSMEs in improving transparency and efficiency of business management as the automation of business processes becomes more assured with the proper application of technology. Therefore, support in the form of digital training is very necessary. The method used in this Community Service Activity is to train MSME actors in Dusun Jayan, Kebon Agung, Imogiri through participatory mentoring. The activity was carried out from January to February 2025. The speakers were UMY students who were involved in the Community Service Activity. There were 3 MSME participants with various types of businesses ranging from culinary businesses, making salted eggs, and bakpia. In this program, participants were given training on digital marketing, using social media for promotion and introducing products more widely. In addition, participants were also guided to create branding to create a strong product identity. The result of this activity is that MSME actors in Dusun Jayan have been able to create logos for their MSME products to be displayed on social media such as TikTok, Instagram, Facebook. Participants also increased their knowledge, especially in understanding the benefits of digital marketing in creating local product marketing strategies. Attractive product branding will increase the number of consumers so that MSME products in Dusun Jayan are increasingly known among the wider community